Drug crime and the port of Rotterdam: about the phenomenon and its approach - Staring, Richard (Organized crime in the 21st century, 2023)
In addition to being the gateway to Europe, the port of Rotterdam’s logistical facilities and services are also abused by organized crime. Large drug seizures and corruption cases have made clear that the port of Rotterdam is a hub for the transit of cocaine. Based on qualitative research, consisting of 73 interviews with public and private actors, an analysis of 10 criminal investigations, and field visits to public and private organizations in the port, this chapter provides insights into the phenomenon of drug trafficking via the port of Rotterdam and the approach to it. This chapter discusses the nature, scope, social organization, and logistical process of drug trafficking, with special attention to the vulnerable locations and sectors in the port complex. In addition, it evaluates the approach to drug crime involving both public and private actors in and around the port of Rotterdam.